Writing history in time of war : Michael Rostovtzeff, Elias Bickerman and the "Hellenization of Asia" - Manning, Joseph Gilbert; Bickerman, E. J. (Elias Joseph), 1897-1981; Rostovtzeff, Michael Ivanovitch, 1870-1952 (Alte Geschichte (Stuttgart, Germany), 2015)
"This book is about two giants of 20th century historiography, Michael Rostovtzeff (1870-1952) and Elias Bickerman (1897-1981) whose lives and careers intersected on many occasions but who have rarely been discussed together. 'Writing History in Time of War' contains, in the main, the results of a lecture given by Pierre Briant and a series of responses to that lecture as the Fourth Annual Michael I. Rostovtzeff Lecture and Colloquium hosted by the Department of Classics at Yale University. Both--Rostovtzeff and Bickerman--were deeply affected by war and exile, and both sought relevance for the modern world in their work and read their own experiences back into their interpretations of the ancient world. This volume adds much new and exciting information about these two scholars, and brings into focus how their own life experiences informed their historical interpretation of the Hellenistic world. Even those who are well familiar with them will find much of value in this volume"-- ‡c Back cover.